Aktivitas Antioksidan Ekstrak Kulit Buah Kakao (Theobroma cacao L.) Pada Perlakuan Suhu dan Lama Penyimpanan - Giskha, Putri Cininta; Ganda Putra, G.P; Semadi Antara, Nyoman (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2023)
This research was conducted to determine effect of temperature and storage time on antioxidant activity of cocoa pod husk extract (Theobroma cacao L.) and to obtain the best combination of storage temperature and storage time that can maintain the antioxidant activity of the extract. The experimental design used in this research was a factorial randomized block design, which are grouped into 2 groups based on the implementation time and consisted of two factors. The first factor was the storage temperature which consisted of 3 level that namely room temperature (27 ±2) ?, cold temperature (5 ±2) ? and freezing temperature (-10 ±2) ?. The second factor was the storage time which consisted of 4 level namely 1, 2, 3, and 4 weeks. The data were analyzed by analysis of variance and continued with Tukey test. The results showed that the temperature and storage time had a very significant effect on total phenol, total flavonoid and antioxidant capacity of cocoa pod husk extract. Interactions between treatments had a very significant effect on total phenol, total flavonoid and antioxidant capacity of cocoa pod husk extract. The best treatment showed that freezing storage (-10 ±2) ? for 1 week can maintain total phenol was 12.32 ± 0.08 mg GAE/g extract, total flavonoid was 4.07 ± 0.09 mg QE/g extract, antioxidant capacity was 6.50 ± 0.02 mg GAEAC/g extract.